2008
DOI: 10.1038/gt.2008.140
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular free tissue transfer for gene delivery: in vivo evaluation of different routes of plasmid and adenoviral delivery

Abstract: Transfer of healthy autologous tissue as a microvascular free flap facilitates reconstruction during ablative cancer surgery. In addition to filling surgical defects, free flaps might concentrate viral vectors at the tumour bed and mediate local therapeutic effects. We evaluated the magnitude, topography and duration of luciferase gene expression after plasmid and adenoviral delivery in rat superficial inferior epigastric (SIE) flaps. For plasmid delivery, luciferase expression was significantly increased by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Time course studies demonstrated a significant reduction in adenoviral gene (GFP) expression at 1 and 3 weeks (figures 2B and 2D) (p < 0.0001) and, in relative terms, was found to have decreased by 58% at 1 week and 84% by 3 weeks compared to the 72 hour time point. This finding is expected due to the transient nature of adenoviral gene expression and validates our earlier work, (13) which showed that adenoviral gene expression typically ceases by 28 days following flap infection. Using RT-QPCR we quantified viral TK expression within flap tissues ( figure 2E) and observed significantly elevated levels of TK mRNA tissues of infected SIEA flaps compared to controls (p<0.05).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Time course studies demonstrated a significant reduction in adenoviral gene (GFP) expression at 1 and 3 weeks (figures 2B and 2D) (p < 0.0001) and, in relative terms, was found to have decreased by 58% at 1 week and 84% by 3 weeks compared to the 72 hour time point. This finding is expected due to the transient nature of adenoviral gene expression and validates our earlier work, (13) which showed that adenoviral gene expression typically ceases by 28 days following flap infection. Using RT-QPCR we quantified viral TK expression within flap tissues ( figure 2E) and observed significantly elevated levels of TK mRNA tissues of infected SIEA flaps compared to controls (p<0.05).…”
Section: Discussionsupporting
confidence: 91%
“…Previous work from our laboratory (13), has shown that the optimal route for introducing a viral vector into a free flap is by intra-arterial injection and that introduction of adenoviral vectors in this manner results in diffuse and durable transgene expression within the flap for up to 28 days. Many therapeutic gene therapy strategies have been proposed for use in conjunction with free flaps (12) and, in this paper, we report the pre-clinical evaluation of a virally directed enzyme prodrug therapy (VDEPT) strategy in the microscopic and macroscopic residual disease settings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As perfusion is not limited to organs but rather to an area with a defined inflow and outflow, free tissue flaps, which are commonly used by plastic and other surgeons in the reconstructive process after radical surgery, are also potential targets for intravascular therapy 26 A further theoretical attraction of this approach is that transduction of a flap with virus may provide a mechanism for local action on microscopic residual disease beyond the flap at the tumour bed and, hence, reduce local recurrence. Overall, animal studies have shown that the effective concentrations of a chemother-apeutic agent achievable within target organs by perfusion-type systems are typically 15–25 times those tolerated in systemic administration, 2731 in which dosages are limited by systemic toxicity.…”
Section: Introductionmentioning
confidence: 99%